Immune response of pearl oysters to stress and diseases. (22nd March 2019) - Adzigbli, Linda; Hao, Ruijuan; Jiao, Yu; Deng, Yuewen; Du, Xiaodong; Wang, Qingheng; Huang, Ronglian
Abstract: Pearl oysters are found in the marine ecosystem. Due to their frequent exposure to microbial pathogens and environmental perturbations, they have developed a multifaceted innate immune system with differentially expressed immune‐related genes in response to a range of stress via vast coordinated immune reactions, such as immune recognition, signal transduction, synthesis of antimicrobial peptides, encapsulation and phagocytosis of the circulating haemocytes. The species are farmed to produce pearls. With the increasing adoption of aquaculture techniques in pearl production, there is the need to understand their culture environment and their immune response mechanisms. Multi‐omic studies have documented responses to nuclei insertion operation, diseases and various environmental conditions in Pinctada fucata martensii (Dunker, 1880), Pinctada maxima (Jameson, 1901), Pinctada margaritifera and Pteria penguin (Roding, 1798). Among the various stressors, nuclei insertion operation has been identified as a prevailing factor modifying gene expression. Other factors include life stage, air exposure, temperature, salinity, metals and organic contaminants. This manuscript details the response mechanism of these pearl oysters to the various stressors.